TEST STANDS AND METHODS FOR INVESTIGATING THE FRETTING PHENOMENON - Stefan Ghimisi (Fiabilitate şi Durabilitate)
Fretting as a damaging way of the surface in contact is known for over 80 years. In the last 20 years there have been important achievements in the experimental research, understanding and description of the mechanisms that lead to this phenomenon. From the definition of the phenomenon of fretting and the study of the influence of various factors on fretting it was concluded that the main factor in the occurrence of fretting is the existence of the relative oscillating movement of small and very small amplitude between the contact surfaces under the action of a normal tasks.